2023
DOI: 10.1038/s41467-023-36119-6
|View full text |Cite
|
Sign up to set email alerts
|

On-demand male contraception via acute inhibition of soluble adenylyl cyclase

Abstract: Nearly half of all pregnancies are unintended; thus, existing family planning options are inadequate. For men, the only choices are condoms and vasectomy, and most current efforts to develop new contraceptives for men impact sperm development, meaning that contraception requires months of continuous pretreatment. Here, we provide proof-of-concept for an innovative strategy for on-demand contraception, where a man would take a birth control pill shortly before sex, only as needed. Soluble adenylyl cyclase (sAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Recently, the application of advanced technologies has helped to move the human fertility field forward, revealing new potential targets for both contraception and fertility, and new compounds as contraceptive candidates (reviewed by (Anderson and Johnston, 2023;Service et al, 2023). A key part of this effort is the development of mechanistic insight and drug candidates that affect the behaviour and properties of human spermatozoa (Balbach et al, 2023;Carlson et al, 2022;Faber et al, 2023;Hau et al, 2022). Towards this end, we have recently developed an automated live human sperm phenotypic, targetagnostic screening platform that can screen 1000s of compounds and identify positive and negative modifiers of sperm function (Gruber et al, 2020;Gruber et al, 2022).…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the application of advanced technologies has helped to move the human fertility field forward, revealing new potential targets for both contraception and fertility, and new compounds as contraceptive candidates (reviewed by (Anderson and Johnston, 2023;Service et al, 2023). A key part of this effort is the development of mechanistic insight and drug candidates that affect the behaviour and properties of human spermatozoa (Balbach et al, 2023;Carlson et al, 2022;Faber et al, 2023;Hau et al, 2022). Towards this end, we have recently developed an automated live human sperm phenotypic, targetagnostic screening platform that can screen 1000s of compounds and identify positive and negative modifiers of sperm function (Gruber et al, 2020;Gruber et al, 2022).…”
Section: Mainmentioning
confidence: 99%
“…This work represents the first version of the STB. Future revisions could contain newly published compounds modulating functions in spermatozoa e.g., a sAC inhibitor TDI-11861 (Balbach et al, 2023), a CatSper inhibitor RU1968 (Schierling et al, 2023), a SLO3 inhibitor (Lyon et al, 2023) or other contributions from the research community. In addition, the STB could present an important resource for testing and benchmarking newly developed drug screening assay.…”
Section: Mainmentioning
confidence: 99%
“…83 Recently, it was reported that a similar compound induced reversible motility defects in sperm that prevented fertility in mice when dosed intraperitoneally. 84 Inhibition of sAC may have promised as an “on-demand” contraceptive for men.…”
Section: Male Contraceptive Mechanism 3: Impairment Of Sperm Functionmentioning
confidence: 99%
“…sAC, a non-membrane bound protein, is found within the cytosol and in several microdomains located inside organelles. ,, In biological systems, CO 2 is maintained in a pH-dependent equilibrium with bicarbonate (HCO 3 – ), and as a result, sAC acts as the nature’s physiological CO 2 /HCO 3 – /pH sensor. , cAMP, produced by sAC in response to changes in CO 2 /HCO 3 – /pH, has been linked to multiple biological functions, such as insulin release from pancreatic β-cells, lysosomal acidification, and regulation of intraocular eye pressure, , in addition to controlling the motility and capacitation of sperm . In regulating these biological functions, sAC is a promising drug target, with sAC inhibitors having several potential therapeutic applications. This group has recently disclosed results describing biological application of a potent sAC inhibitor. …”
Section: Introductionmentioning
confidence: 99%